(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we give some examples of k-ideals of ternary semirings. We examine the results of k-ideals by distinguished classes in ternary semirings, which include k-maximal, k-prime and k-semiprime.